Rules of origin for services in economic integration agreements : a case study of SADC - Naidu, Vahini (GSB: Faculty, 2016)
The origin of services is increasingly relevant against the backdrop of technological innovation and global value chains. Rules of origin for trade in services are especially important in Economic Integration Agreements, which are proliferating in response to the changes in global trade and production. The Southern African Development Community commenced the Protocol on Trade in Services negotiations in April 2012 with the objective of creating an integrated regional market for services. This study examines the current and dominant approaches to the formulation of rules of origin for trade in services in twenty five (25) Economic Integration Agreements with the purpose of making recommendations, to develop further, the definition of "substantial business operations" for the SADC Protocol on Trade in Services. It concludes, first, that the type best suited for SADC is a rule of origin designed to address broader socio-economic goals in the region. Second, the criteria used to define substantial business operations in the Mainland-Hong Kong, China CEPA provides a basis which SADC can consider as a key determinant of origin, in order to prevent free-riders from benefiting from the trade preferences under the SADC Protocol on Trade in Services. Lastly, the effectiveness of rules of origin will depend on domestic regulation and regional monitoring, evaluation and enforcement mechanisms to support and regulate investments in the services sectors.